Identifikasi dan Mitigasi Risiko Dalam Proses Investigatif: Studi Kasus Film The Manipulated - Fajar, Deddy Ahmad; Novara, Divanda Jingga; Ning Atik, Sephia Puji; Mahmudah, Kholidatul; Munawaroh, Faridatul; Sanjaya, Nanda Dea; Anisiyah, Dwi Maulid (CV. ITTC INDONESIA, 2025)
Risk management plays a crucial role in criminal investigation procedures, particularly in dealing with uncertainty and manipulation as depicted in the film The Manipulated. This study aims to systematically apply the ISO 31000 framework to analyze investigative risks depicted in the film The Manipulated. The research method used is a qualitative case study approach. Data collection was carried out through structured observation involving a minimum of three screenings of the film and document analysis, which aimed to identify risk elements in the operational, investigative, and interpersonal dimensions. Data were collected through structured observation and document analysis, for a holistic understanding of risk mitigation strategies. The results of the discussion identified crucial risks that interfere with investigator objectivity, namely the risk of data reliability, manipulation of physical evidence, and human risk due to psychological pressure. Recommended mitigation includes strengthening internal control of evidence and implementing risk control behavior (mental stability and objectivity), in accordance with the principles of risk treatment ISO 31000. The conclusion of this study is that the implementation of risk management (identification, analysis, evaluation, and mitigation) is vital to controlling uncertainty and maintaining the integrity of the investigation. This film is effective as a learning medium that emphasizes the obligation of investigators to manage human factors and systematize processes so that decisions are taken accurately.